System login authentication using voice recognition and other AI methods / Zati Hakim Azizul Hasan - Zati Hakim, Azizul Hasan (2000)
As computer becomes a commodity in work places and households appliances used by all - be it male or female young or old - the issue of security and privacy are increasing from day to day. Today, every user wishes for a better way to protect sensitive data. For all the talk about beefing up system security, the most effective way to breach a user's personal files and applications is to guess his or her password. That's because in the interest of easy recall, familiar terms are most preferred by users in general when it come too remembering a password. In fact, most passwords can be found on paper scraps taped to the desk or under the keyboard. This is where this project bores a significant impact on system security. Voice authentication, one of the most popular biometric methods in handling fraud and data intruders, perhaps is the very thing that could change everything Still one of the leading Exciting areas of modern computer science research, voice recognition and authentication is also one of the most difficult. The sheer variety and complexity of a word makes recognizing similar words very difficult even though it is said by the same individual. Nevertheless it is still the cheapest and yet effective approach to user's authentications because of the simplicity of the devices used - everyone has a microphone or a telephone attached to their own computer and everyone has a unique vocal tract that cannot be changed. Whenever there is need for security, there exist an opportunity for this unique technology It’s up to us to accept its uniqueness and ubiquity- a powerful combination that can further allow for powerful solution.